2005
DOI: 10.1039/b501354b
|View full text |Cite
|
Sign up to set email alerts
|

A case study for the provision of measurement traceability and measurement uncertainty for the South African reference materials

Abstract: The South African Reference Materials (SARMs) have traditionally been certified through interlaboratory studies involving reputable national and international laboratories. The ISO definition of a Certified Reference Material (CRM) has changed recently. In view of these changes re-certification of the SARMs with the use of primary methods to provide measurement traceability and complete evaluation of the uncertainties associated with the methods are urgently needed. The CSIR-National Metrology Laboratory of So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
2
12
0
Order By: Relevance
“…Many of the widely used rock RMs were characterised decades ago using the best practices available at the time of their production. In the determination of trace elements in particular, technical advances now permit more reliable and precise measurements (Dulski 2001, Raczek et al 2001, Makishima et al 2002, Pin et al 2003, Botha et al 2005, Pearce et al 2007. As an outcome, many older RMs lack values for many constituents or they have large uncertainties, limiting their applicability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the widely used rock RMs were characterised decades ago using the best practices available at the time of their production. In the determination of trace elements in particular, technical advances now permit more reliable and precise measurements (Dulski 2001, Raczek et al 2001, Makishima et al 2002, Pin et al 2003, Botha et al 2005, Pearce et al 2007. As an outcome, many older RMs lack values for many constituents or they have large uncertainties, limiting their applicability.…”
mentioning
confidence: 99%
“…As a consequence, most of the available elemental IDMS values were published after the rock RMs were issued. An example is the work carried out by Botha et al (2005Botha et al ( , 2007 and Botha (2010), for eight trace elements (Ba, Cd, Cu, Mo, Ni, Pb, Sr and Zn) in three South African Reference Materials (SARM) certified by the Council for Mineral Technology (MINTEK), in the 1970s. Vogl (2012) compared the capabilities of single, double and triple IDMS and concluded that the three techniques can produce equally accurate results.…”
mentioning
confidence: 99%
“…The older RMs from South Africa (Steele et al. 1978) have been recently analysed by Botha et al. (2005, 2007) for a few trace elements using so‐called ‘definitive’ techniques such as isotope dilution‐ICP‐MS (ID‐ICP‐MS).…”
Section: Resultsmentioning
confidence: 99%
“…1995, b Govindaraju 1995, c Steele et al. 1978, d Botha et al. 2005, e Govindaraju 1984); the subscripts lit and tw are literature and this work, respectively; n/a information not available.…”
Section: Resultsmentioning
confidence: 99%
“…Uncertainty in the certified value-Uncertainty in the certified values was calculated in a manner consistent with the ISO Guidelines for the Expression of Uncertainty in Measurement (GUM) 27 . The procedure used was developed from the guidelines provided by NIST, 34 Eurachem 35 , and from examples given by Ellison et al 36 , Botha et al 37 and Sturgeon et al 32 The uncertainty for our analysis of SRM 1486 Bone Meal is also given; it was approximately twice the uncertainty as stated by NIST on the certificate.…”
Section: Sample Drying Proceduresmentioning
confidence: 99%